Genetic Analysis of Yield and Related Characters of Lablab Bean - Rony, Md. Borhan Uddin; Islam, AKM Aminul; Rasul, Md. Golam; Zakaria, Mohammad (Journal of Nepal Agricultural Research Council, 2019)
An experiment was conducted with a view to determine the nature and extent of gene action of yield and yield related characters of lablab bean. Five parents and their 10 F1s synthesized from 5 x 5 half diallel cross were evaluated in a Randomized Complete Block Design with three replications. The analysis of variance showed that the difference among the genotypes (parents and F1s) were highly significant for all the characters which revealed the presence of wide variability among the genotypes under this study. Hayman’s ANOVA (modified by Jones) suggested that the presence of additive and dominance gene actions for all the characters. The ‘Vr-Wr’ graph indicated partial dominance for the characters viz. days to first inflorescence appearance, days to first flowering, days to pod maturity, days to seed maturity, number of nodes per inflorescence, edible pod length, edible pod breadth, edible pod weight and pod yield per plant. Over dominance was observed for number of inflorescences per plant, number of pods per inflorescence and hundred seed weight. Complete dominance was observed only for number of pods per plant in lablab bean. As the development of hybrid variety is not possible in lablab bean, diallel selective mating system may be adopted for improvement of yield traits by using knowledge of gene actions. The hybrids with predominant additive gene action for yield related traits may be advanced to obtain transgressive segregants and pure lines for higher pod yield per plant.